Effect of fins on phase change material melting and solidification in cylindrical containers - Anthonysamy, Nicholas (Nanyang Technological University, 2022)
Phase Change Material (PCMs) is suitable to be used for waste heat recovery applications due to their capability to store energy. The drawback of using PCMs is low heat transfer rate due to its low thermal conductivity. This can be overcome by utilizing fins in the heat exchanger. An experiment setup is created to carry out the test and for future testing. The new setup is design to handle Heat Transfer Fluid between 0˚C to 100˚C and can be used to test both charging and discharging cycle. In this study, experiment will be conducted with Thermal Energy Storage (TES) in horizontal position with Rubitherm 42(the volume kept constant at 160ml) used as PCMs material and the flow of Heat transfer fluid (HTF) maintain at 0.5l/min. A finless tube and three tube with fin will be used to carry out the experiment and was be subjected to melting and solidification cycle. The data from the experiment will be analyzed. The amount of time for the all the thermocouples in TES unit to achieve melting temperature (43˚C) and solidification temperature (38˚C) was used to determine level of enhancement. Numerical simulation of the experiment can be carried out in the future and the result can be match with the experiment result to validate the simulation setting as well as the results of subsequent simulation for various fin designs.